Nutrient Enrichment Mediates the Relationships of Soil Microbial Respiration with Climatic Factors in an Alpine Meadow. (12th August 2015) - Zong, Ning; Jiang, Jing; Shi, Peili; Song, Minghua; Shen, Zhenxi; Zhang, Xianzhou
Abstract : Quantifying the effects of nutrient additions on soil microbial respiration (R m ) and its contribution to soil respiration (R s ) are of great importance for accurate assessment ecosystem carbon (C) flux. Nitrogen (N) addition either alone (coded as LN and HN) or in combination with phosphorus (P) (coded as LN + P and HN + P) were manipulated in a semiarid alpine meadow on the Tibetan Plateau since 2008. Either LN or HN did not affect R m, while LN + P enhanced R m during peak growing periods, but HN + P did not affect R m . Nutrient addition also significantly affected R m / R s, and the correlations of R m / R s with climatic factors varied with years. Soil water content (Sw) was the main factor controlling the variations of R m / R s . During the years with large rainfall variations, R m / R s was negatively correlated with Sw, while, in years with even rainfall, R m / R s was positively correlated with Sw. Meanwhile, in N + P treatments the controlling effects of climatic factors on R m / R s were more significant than those in CK. Our results indicate that the sensitivity of soil microbes to climatic factors is regulated by nutrient enrichment. The divergent effects of Sw on R m / R s suggest that precipitation distribution patterns are key factors controlling soil microbial activities and ecosystem C fluxes in semiarid alpine meadow ecosystems.